Joel Kahn and an intercultural interpretation of Southeast Asian modernity. (September 2019) - Goh, Beng-Lan
Joel S. Kahn's writings on Southeast Asian modernity are marked by an insistence on the inseparability and equality of Western and Southeast Asian thought and social–cultural experiences. His work explores continuities, breaks, and contradictions within and across each of these expansive worlds, showing omitted narratives to be no less constitutive of the modern. Drawing on conundrums over how to translate across irreducible sets of differences without taming difference under familiar or universal categories in my own study of radical politics in contemporary Malaysia, I explore how Kahn's writings on Southeast Asian modernity provide a possible resolution to the problems of relativism and canonical predeterminations in the reconciliation of cultural difference. I argue that in a multipolar, uncertain, and divided age, Kahn's work provides us with an inspiration to speak across spatially located ethical divides, bringing converging and contrasting critical outlooks together for mutual competition and enrichment of intercultural understandings of modern cultural diversity and human fulfillment without reinventing the place of power either in the West, Southeast Asia, or anywhere else.